Could Postnatal Age–Related Uridine Diphosphate Glucuronic Acid Be a Rate‐Limiting Factor in the Metabolism of Morphine During the First Week of Life?. (10th May 2019) - Liu, Tao; Lewis, Tamorah R.; Moore, Jason N.; Kraft, Walter K.; Gauda, Estelle B.; Sartori, David; Moody, David E.; Gobburu, Jogarao V. S.; Ivaturi, Vijay
Abstract : Neonates experience dramatic changes in the disposition of drugs after birth as a result of enzyme maturation and environmental adjustment, challenging therapeutic decision making. In this research, we establish postnatal age, postmenstrual age, and body weight as physiologically reasonable predictors of morphine's clearance in neonates. By integrating knowledge of bilirubin, morphine, and other drugs metabolized by glucuronidation pathways from previously published studies, we hypothesize that uridine diphosphate glucuronic acid, a postnatal age–dependent sugar, plays an important role in the metabolism of morphine during the first week of life. This finding can be extended to other drugs metabolized by uridine diphosphate glucuronosyltransferase pathways in neonates and thus has important clinical implications for the use of drugs in this population.